2019
DOI: 10.7150/ijms.34440
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Substrates for Cell-Based Tissue Engineering of Human Corneal Endothelial Cells

Abstract: Corneal endothelial tissue engineering aims to find solutions for blindness due to endothelial dysfunction. A suitable combination of endothelial cells, substrates and environmental cues should be deployed for engineering functional endothelial tissues. This manuscript reviews up-to-date topics of corneal endothelial tissue engineering with special emphasis on biomaterial substrates and their properties, efficacy, and mechanisms of supporting functional endothelial cells in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…The substrate composition and topography have a crucial impact on the success of CEC culture because they stimulate the attachment, migration, proliferation, and overall function of the cultured CECs [ 17 , 61 ]. Due to the poor adherence of CECs to uncoated culture dishes, various biological, biosynthetic, or synthetic substrates for CEC expansion have been tested up to now, as reviewed elsewhere [ 62 64 ] (Table 1 ). The ideal substrate should mimic the composition (collagens 4–6, 8, 18, fibronectin, laminin, thrombospondin) and topography of DM [ 64 , 65 ], therefore helping to maintain the CEC phenotype and function and promoting CE regeneration after injury [ 66 ].…”
Section: In Vitro Expansion Of Cells From Donor Tissuementioning
confidence: 99%
See 3 more Smart Citations
“…The substrate composition and topography have a crucial impact on the success of CEC culture because they stimulate the attachment, migration, proliferation, and overall function of the cultured CECs [ 17 , 61 ]. Due to the poor adherence of CECs to uncoated culture dishes, various biological, biosynthetic, or synthetic substrates for CEC expansion have been tested up to now, as reviewed elsewhere [ 62 64 ] (Table 1 ). The ideal substrate should mimic the composition (collagens 4–6, 8, 18, fibronectin, laminin, thrombospondin) and topography of DM [ 64 , 65 ], therefore helping to maintain the CEC phenotype and function and promoting CE regeneration after injury [ 66 ].…”
Section: In Vitro Expansion Of Cells From Donor Tissuementioning
confidence: 99%
“…It was shown that a replacement of the DM alone can be sufficient to induce the regeneration of host CECs in vivo [ 67 ]. In recent studies, an FNC coating mix® [ 11 , 40 , 45 ] and collagen 1 and 4 [ 21 , 62 , 68 ] have been the most widely used substrates for CEC cultures.…”
Section: In Vitro Expansion Of Cells From Donor Tissuementioning
confidence: 99%
See 2 more Smart Citations
“…Here, we will specifically emphasize the development of cornea mimics that use cells in combination with natural biomaterials that explore patient outcomes in animal models or serve as in vitro tissue models. Many cell types have been investigated for use in corneal tissue engineering, including corneal endothelial cells (CEnCs), corneal epithelial cells (CEpCs), corneal epithelial stem cells (CEpSCs), keratocytes (CKs), mesenchymal stem cells (MSCs), adipose-tissue derived stem cells (ASCs), and embryonic-derived stem cells [ 132 , 133 , 134 ].…”
Section: Engineering a Cornea Mimetic: Cell Types And Their Functionmentioning
confidence: 99%